2017
DOI: 10.1186/s13256-017-1322-3
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke complicating thrombolytic therapy with tenecteplase for ST elevation myocardial infarction: two case reports

Abstract: BackgroundHemorrhagic complications are quite common in the rare cases where thrombolysis is performed. Ischemic stroke in the aftermath of thrombolysis for a ST elevation myocardial infarction is a very rare and paradoxical complication. With these observations in mind we report two interesting cases of ischemic stroke which occurred after fibrinolytic therapy with tenecteplase for a ST elevation myocardial infarction.Case presentationThe first case was a 56-year-old African man who presented with an acute in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…An interesting finding in the group of patients who received fibrinolysis was a case of ischemic cerebrovascular event not related to atrial fibrillation, this is a very rare complication with a not well clarified pathophysiology, although several mechanisms have been proposed [ 23 ]. A large registry indicated that the incidence of in-hospital ischemic stroke after STEMI is about 1.2%, increasing the risk of mortality, and the factors associated include: age, female gender, atrial fibrillation, history of cerebrovascular accident, heart failure, diabetes mellitus, chronic renal failure, carotid artery disease, aortic disease, left ventricle thrombus, left ventricle aneurysm, acute or chronic deep venous thrombosis/pulmonary embolism, hypercoagulable state, and coronary artery bypass grafting [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding in the group of patients who received fibrinolysis was a case of ischemic cerebrovascular event not related to atrial fibrillation, this is a very rare complication with a not well clarified pathophysiology, although several mechanisms have been proposed [ 23 ]. A large registry indicated that the incidence of in-hospital ischemic stroke after STEMI is about 1.2%, increasing the risk of mortality, and the factors associated include: age, female gender, atrial fibrillation, history of cerebrovascular accident, heart failure, diabetes mellitus, chronic renal failure, carotid artery disease, aortic disease, left ventricle thrombus, left ventricle aneurysm, acute or chronic deep venous thrombosis/pulmonary embolism, hypercoagulable state, and coronary artery bypass grafting [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological processes underlying ischemic strokes following AMI are complex. Ischemia causes a systemic procoagulant response, facilitating the formation of cardiac thrombuses and embolization [12] . The patient had an inferior MI, which is unusual as a cause of thrombus formation and can be a possible explanation for the acute ischemic stroke due to the brinolysis of that thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…In another analysis, anterior wall MI was associated with an increased risk of stroke (AOR, 1.16; 95% CI, 1.10-1.22; p=0.001). "Echocardiographic studies indicate that most patients with visible mural thrombi have anterior wall infarction, whereas patients with good left ventricular function and inferior wall infarction rarely have detectable thrombi" [8,9]. "Substance abuse, including alcohol abuse and cocaine abuse/dependence, has also been linked to post-MI CVA" [10].…”
Section: Fig 2 Ct Scan Showing a Right Sylvian Artery Stroke With Sub...mentioning
confidence: 99%